A Brief Review of circRNA Biogenesis, Detection, and Function - Liang, Ying; Liu, Niannian; Yang, Le; Tang, Jianjun; Wang, Yinglong; Mei, Meng (Current genomics, 2021)
Circular RNA (circRNA) is a non-coding molecule produced through alternative splicingof one or more exons of a gene in the presence of an RNA-induced silencing complex (RISC).Its formation depends on complementary intron sequences on both sides of the circularized sequence.CircRNA functions as a sponge for miRNA, playing the role of the transcriptional regulatoror potential biomarker. It has an impact on fetal growth and on synaptic facilitation in the brain.In this review, we illustrate biogenesis mechanisms, characteristics, and functions of cirRNAs. Wealso summarize methods using sequence feature and RNA next-generation sequencing data for circRNAprediction. Finally, we discuss the state of the research on circRNA in diseases, which willbring new contributions to future disease treatments.